THE EFFECT OF EMPLOYEE ENGAGEMENT, EMPLOYEE TRAINING AND ORGANIZATIONAL CULTURE ON EMPLOYEE RETENTION AT UD BAHARI JAYA, LUMAJANG REGENCY - Evilawati, Fentiana; Azhad, M. Naely; Diansari R.P, Tatit (Universitas Muhammadiyah Tangerang, 2024)
UD Bahari Jaya Lumajang Regency will experience fluctuating employee retention in 2023. This research aims to examine the influence of employee involvement, employee training and organizational culture on employee retention at UD Bahari Jaya Lumajang Regency. This research uses descriptive quantitative methods that are associative in nature. The data source in this research is a Likert scale questionnaire. The population used is all employees at UD Bahari Jaya, Lumajang Regency. The sampling technique used was saturated sampling, so the sample consisted of 50 respondents. The analysis method uses a series of multiple linear regression analysis. This research shows that employee involvement has a positive and significant effect on employee retention at UD Bahari Jaya, Lumajang Regency; employee training has a positive and significant effect on employee retention at UD Bahari Jaya, Lumajang Regency; organizational culture has a positive and significant effect on employee retention at UD Bahari Jaya, Lumajang Regency; Employee involvement, employee training, and organizational culture simultaneously have a positive and significant effect on employee retention at UD Bahari Jaya, Lumajang Regency. The variables of employee engagement, employee training, and overall organizational culture can influence employee retention by 78.7%. The remaining 21.3% is influenced by other factors not included in the scope of this research.